A dimensão geográfica das romarias da terra do Paraná - Valcarenghi, Alexandre Roberto (2013)
This research addresses the geographical size of the Earth Pilgrimages of Paraná - occurring since 1985 - with emphasis on the agricultural aspects, especially the fight and stay on earth. The "local" to the completion of Pilgrimages, hymns, songs, speeches, political and religious rituals are laden with geographic content and constitute the main axis of this study. The main objectives were to analyze the Pilgrimages were produced Earth Paraná, by whom and for whom. By analyzing the 26 th Pilgrimage Earth Paraná , which happened in August 2012, we sought through interviews and informal conversations, analyzing the profile of the pilgrims land , paying attention to the following aspects: their place of origin, its form displacement, their belonging to religious and political groups and their aspirations as pilgrims. Maps, photos, posters, pictures and videos were used, and if these had access through TV documentaries produced by the Who . The results proved the importance and relevance of Earth Pilgrimages of Paraná in Paraná represent the agrarian landscape.